SOME PROBLEMS ORIGINATED AT THE ENDEAVOUR FOR OBJECTIVE EVALUATION OF STUDENTS - MONKA, Peter; MONKOVA, Katarina (Trends in education, 2009)
The article deals with investigation of possibilities at increasing of objective examination of student examination and evaluation of student extasciiacutes knowledges in educational process. There are specified some problems originated at the endeavour for objective evaluation of students in the article. The article is direct supported from grants KEGA no.3/5172/07 and KEGA no.3/5173/07 of Cultural and Educational Grant Agency of Ministry of Education of Slovak republic.
Keywords: examination; objective evaluation; key powers.